2008
DOI: 10.1179/146431508790559715
|View full text |Cite
|
Sign up to set email alerts
|

Information about Support Services for Families of Young Children with Hearing Loss: A Review of Some Useful Outcomes and Challenges

Abstract: This paper is concerned with reviewing some useful effects of information about

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…A 3D model would best represent the interaction and merging of the conceptual framework and the environment to support it. has an important role in helping parents provide assistance to their children (Åsberg, Vogel, & Bowers, 2007;Bradham, Houston, Guignard, & Hoffman, 2011;Brown & Remine, 2008;Dalzell, Nelson, Haigh, Williams, & Monti, 2007;Eleweke, Gilbert, & Bays, 2008;Fitzpatrick, Graham, Durieux-Smith, Angus, & Coyle, 2007;Fitzpatrick, 2010;Hardonk et al, 2013;Jackson, Wegner, & Turnbull, 2010;Larson, Munoz, DesGeorges, Nelson, & Kennedy, 2012;Lederberg & Golbach, 2002;Muñoz, Blaiser, & Barwick, 2013;Poon & Zaidman-Zait, 2014;Sipal & Sayin, 2012). When a child is diagnosed with a hearing loss, the majority of these children will be born to parents with typical hearing who were not expecting the diagnosis (Bagatto, Scollie, Hyde, & Seewald, 2010;Mitchell & Karchmer, 2004 The international consensus document provided the impetus for this research study.…”
Section: Future Directionsmentioning
confidence: 99%
“…A 3D model would best represent the interaction and merging of the conceptual framework and the environment to support it. has an important role in helping parents provide assistance to their children (Åsberg, Vogel, & Bowers, 2007;Bradham, Houston, Guignard, & Hoffman, 2011;Brown & Remine, 2008;Dalzell, Nelson, Haigh, Williams, & Monti, 2007;Eleweke, Gilbert, & Bays, 2008;Fitzpatrick, Graham, Durieux-Smith, Angus, & Coyle, 2007;Fitzpatrick, 2010;Hardonk et al, 2013;Jackson, Wegner, & Turnbull, 2010;Larson, Munoz, DesGeorges, Nelson, & Kennedy, 2012;Lederberg & Golbach, 2002;Muñoz, Blaiser, & Barwick, 2013;Poon & Zaidman-Zait, 2014;Sipal & Sayin, 2012). When a child is diagnosed with a hearing loss, the majority of these children will be born to parents with typical hearing who were not expecting the diagnosis (Bagatto, Scollie, Hyde, & Seewald, 2010;Mitchell & Karchmer, 2004 The international consensus document provided the impetus for this research study.…”
Section: Future Directionsmentioning
confidence: 99%
“…Following the steps of BCW, the current study identified that the provision of individualised information and support to families of children with HL needs to be improved in order to provide a family-centred service during the transition to EI. Similar to the current study, literature has previously identified that parents of children with HL require adequate and individualised information (Eleweke, Gilbert, Bays, & Austin, 2008; and encourage professionals to be sensitive to families' individual needs (Brown, Abu Bakar, Rickards, & Griffin, 2006). Therefore, in the current study, the administration of a needs assessment was identified as an opportunity to meet the needs of families to receive individualised information and support.…”
Section: Discussionsupporting
confidence: 54%
“…Davis, A., Davis, K., & Mencher, G. (2009). Eleweke, C. J., Gilbert, S., Bays, D., & Austin, E. (2008). Information about support services for families of young children with hearing loss: A review of some useful outcomes and challenges.…”
Section: Rationale Aims and An Overview Of The Methodology Of The Tmentioning
confidence: 99%
See 2 more Smart Citations